Acrodysostosis - Silve, C.; Clauser, E.; Linglart, A. (Hormone and Metabolic Research, 2012)
Acrodysostosis refers to a group of rare skeletal dysplasias that share in common characteristic clinical and radiological features including brachydactyly, facial dysostosis, and nasal hypoplasia. In the past, the term acrodysostosis has been used to describe patients with heterogeneous phenotypes, including, in some cases, patients that today would be given alternative diagnoses. The recent finding that mutations impairing the cAMP binding to PRKAR1A are associated with “typical” acrodysostosis and hormonal resistance initiates the era where this group of disorders can be categorized on a genetic basis. In this review, we will first discuss the clinical, radiologic, and metabolic features of acrodysostosis, emphasizing evidence that several forms of the disease are likely to exist. Second, we will describe recent results explaining the pathogenesis of acrodysostosis with hormonal resistance (ADOHR). Finally, we will discuss the similarities and differences observed comparing patients with ADOHR and other diseases resulting from defects in the PTHR1 signaling pathway, in particular, pseudohypoparathyroidism type 1a and pseudopseudohypoparathyroidism.
Keywords: PRKAR1A; proteine kinase A; parathyroid hormone (PTH)/PTHrP; hormonal resistance; GNAS/Gsα; pseudohypoparathyroidism (PHP); PDE